(untitled) (CoverAge: Journal of Strategic Communication, 2024)
In the era of information abundance, especially after the advent of social media, it is more difficult toselect and sort accurate and credible information. For this reason, guidelines are needed that can guidesocial media consumers which information is accurate and which information is false. For this reason, it is necessary to fact-check the information circulating on social media. The existence of communities and fact-checker organizations is a necessity nowadays. However, how communities and fact-checking organization scarry out their standard procedures should be of particular concern. What are the principles, procedures, and mechanisms for checking facts between communities and fact-checking organizations, the focus of this research. The results of the study show that there are similarities and atthe same time differences in terms of fact checking carried out by three fact-checking entities, namely the Ministry of Communication and Informatics, Mafindo, and Jabar Saber Hoaks. The similarity ofprinciples, procedures, mechanisms and methods of checking facts indicates that there is an effort touphold the discipline of fact verification. In addition, there are similarities in terms of verification and fact-checking results due to the similarity of procedure references. However, in terms of differences, itcan be seen in the way of labeling or flagging which can have an impact on public confusion inunderstanding the results of fact-checking hoaxes on social media. The results of fact checking carriedout by the three fact-checking entities in Indonesia reflect a constructive effort to educate the public about the importance of recognizing the characteristics and types of hoaxes that often circulate on social media.